Physiological strategies for handling summer water stress differ among co-existing species and between juvenile and mature trees - Bryant, Kelsey; Fredericksen, Brett; Hudiburg, Tara; Rosenthal, David (Frontiers in Forests and Global Change, 2023)
Determining tree response to climate stress is critical for predicting changes in forest carbon dynamics as well as tree mortality. In temperate deciduous forests, describing this response is complicated by the complex diversity of leaf and wood characteristics among co-existing species. Furthermore, because of the inherent logistical limitations of measuring mature forest trees, many carbon models and stress-response studies are informed by physiological data collected from juvenile trees (seedlings or saplings). However, the extent to which juvenile and mature trees differ in their physiological responses to water stress is not well documented under natural conditions. The majority of carbon sequestered in a forest is in mature trees; therefore, direct canopy measurements comparing responses to climate in juvenile and mature trees would allow us to more accurately predict changes in ecosystem carbon uptake. Here, we present data describing the physiological responses to summer water stress in juvenile trees of six temperate deciduous species. Our results indicate that species exhibited variation and plasticity in stress hydraulic parameters yet maintained similar rates of carbon uptake. We demonstrate how integrative photosynthetic parameters, such as photosynthetic capacity and quantum efficiency of photosystem II, are beneficial for wholistically displaying physiological responses at the leaf level. We further compared seasonal patterns of leaf water potential during decreasing soil water availability between the juvenile trees and co-existing mature trees of the same species. Our data reveal that while some species remain static in their hydraulic behavior from the juvenile to adult stage, other species are dynamic between life stages. Models, as well as experimental studies examining tree response to stressors, should plan for plasticity in physiological parameters among co-existing species, and should further allow variability between life stages for particular species. The capacity to effectively inform models from data collected in mature trees will inevitably lead to improved predictions of tree mortality and forest carbon trajectories.